THE MESA OF OYBIN (UPPER LUSATIA, GERMANY) AND ITS IMPORTANCE FOR GEOLOGY AND GEOTOURISM - Jiří BERÁNEK; Beáta KORANDOVÁ; Dana VRUBLOVÁ (Geo Journal of Tourism and Geosites, 2019)
The aim of this article is to call attention to the most interesting place in the Zittau Mountains (Upper Lusatia, Germany), the mesa of Oybin. Besides ruins of the medieval Oybin castle and monastery, there are several examples of geological processes connected with the Upper Cretaceous sedimentation and later erosion in local quartz sandstones. The mesa itself provides an excellent witness of the deposition cycles, probable subaquatic landslides as well as various examples of later weathering. Selected features have been photographed, consulted with relevant literary sources and their probable origin discussed within the text. Photos of selected phenomena are included and explained in details. Visibly denoted and enlightened geological features could increase the tourist attractiveness of the mesa in terms of a complete description of this interesting mountain.